Volatile organic compound emission from holm oak infested by gypsy moth larvae: evidence for distinct responses in damaged and undamaged leaves (Tree Physiology, 2007)
Foliage of Quercus ilex L. (holm oak), a widespread Mediterranean species, constitutively emits large quantities of a complex genotype-dependent mixture of volatile organic compounds (VOCs). During a mass outbreak of gypsy moth (Lymantria dispar L.) in southern France, we examined the effects of gypsy moth feeding on VOC production from whole apices and single leaves of Q. ilex. Feeding induced the emission of new VOCs at rates up to 240 ng m−2 s−1 (16% of the total VOC release), which mainly consisted of sesquiterpenes, a homoterpene and a monoterpene alcohol. The new compounds were emitted after a delay of several hours following infestation and their production declined rapidly when caterpillars were removed. Undamaged leaves of infested trees emitted new VOCs, but with a different composition to those of damaged leaves and at lower rates. Neither caterpillars nor caterpillar excrement released VOCs. Emission of constitutive VOCs by undamaged leaves of infested trees temporary increased by up to 30%, whereas, in damaged leaves, they remained stable and decreased after some days when necrotic spots occurred around the feeding sites. In continuous light and at constant temperature, emissions of new VOCs showed a marked diurnal cycle, whereas those of constitutive VOCs did not. The results suggest that induced VOCs make a significant contribution to the atmospheric VOC load and may mediate trophic interactions. The observed differential local and systemic responses in composition, quantity and time courses of emissions mirror the existence of several regulation processes triggered by different signaling compounds and elicitors.
10.1093/treephys/27.10.1433